2012
DOI: 10.1111/j.1365-2427.2012.02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA taxonomy to investigate the ecological determinants of plankton diversity: explaining the occurrence of Synchaeta spp. (Rotifera, Monogononta) in mountain lakes

Abstract: Summary 1. The occurrence of unresolved complexes of cryptic species may hinder the identification of the main ecological drivers of biodiversity when different cryptic taxa have different ecological requirements. 2. We assessed factors influencing the occurrence of Synchaeta species (monogonont rotifers) in 17 waterbodies of the Trentino‐South Tyrol region in the Eastern Alps. To do so, we compared the results of using unresolved complexes of cryptic species, as is common practice in limnological studies base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…Cryptic species complexes in rotifers are often inferred based on the mitochondrial COI (Suatoni et al, 2006;Obertegger et al, 2012Obertegger et al, , 2014Leasi et al, 2013;Fontaneto, 2014;Malekzadeh-Viayeh et al, 2014). We extracted DNA from single live individuals with 35 ll of Chelex (InstaGeneMatrix, Bio-Rad, Hercules, CA, USA).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 99%
“…Cryptic species complexes in rotifers are often inferred based on the mitochondrial COI (Suatoni et al, 2006;Obertegger et al, 2012Obertegger et al, , 2014Leasi et al, 2013;Fontaneto, 2014;Malekzadeh-Viayeh et al, 2014). We extracted DNA from single live individuals with 35 ll of Chelex (InstaGeneMatrix, Bio-Rad, Hercules, CA, USA).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 99%
“…Another issue that is especially relevant for microevolutionary studies with monogonont rotifers is the existence of cryptic species. Since the discovery of cryptic species in Brachionus plicatilis (Gómez & Serra, 1995;Gómez et al, 2002), the number of rotifer taxa known to be composed of cryptic species has steadily increased during the last decade (Walsh et al, 2009;Obertegger et al, 2012). Furthermore, several studies have provided evidence for substantial ecological segregation among such species (Gabaldón et al, 2015a;Papakostas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Keratella, Polyarthra; Stemberger & Gilbert, 1987). The identification of cryptic species with different environmental needs and different competitive abilities as seen for S. pectinata species complex (Obertegger et al, 2012), Brachionus plicatilis species complex (Montero-Pau et al, 2011), and P. dolichoptera complex (Obertegger et al, 2014), respectively, could further elucidate the importance of gross morphologically-based functional traits. In fact, it has recently been shown that different cryptic species of P. dolichoptera show seasonal succession in Lake Tovel (Obertegger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%